The Impact of the Transcendental Meditation Program on Government Payments to Physicians in Quebec: An Update - Herron, Robert E.; Hillis, Stephen L. (American journal of health promotion, 2000)
Purpose. To determine whether practice of the Transcendental Meditation (TM) technique can affect medical expenses. Design. The evaluation was a quasi experimental, longitudinal, cost-minimization study. Setting. Province of Quebec, Canada. Subjects. This study involved 1418 Quebec health insurance enrollees who practiced the TM technique compared with 1418 subjects who were randomly selected from enrollees of the same age, sex, and region. TM subjects had chosen to begin the technique prior to learning about and choosing to enter the study. Measures. This 14-year, pre- and postintervention study retrospectively assessed government payments to physicians for treating the TM and comparison groups. Other medical expense data for individuals were unavailable. Data were inflation-adjusted. For each subject, least squares regression slopes were calculated to estimate pre- and postintervention annual rates of change in payments. We compared the groups' means and 1%, 5%, and 10% trimmed means (robust estimators) of the slopes. Results. Before starting meditation, the yearly rate of increase in payments between groups was not significantly different (p > .17). After commencing meditation, the TM group's mean payments declined 1% to 2% annually. The comparison group's payments increased up to 11. 73% annually over 6 years. There was a 13. 78% mean annual difference (p = .0017). Conclusions. The results suggest that the TM technique reduced payments to physicians between 5 % and 13 % annually relative to comparison subjects over 6 years. Randomized studies are recommended.